Дослідження точності розв’язання дискретних некоректних задач методом випадкових проекцій - Ревунова, О.Г. (Управляющие системы и машины, 2018)
Для розв’язання дискретних некоректних задач на основі аналітичного усереднення випадкового проектування розроблено метод визначення оптимальної розмірності випадкової матриці, який забезпечує помилку розв’язку таких задач, близьку до мінімальної. Для решения дискретных некорректных задач на основе аналитического усреднения случайного проецирования разработан метод определения оптимальной размерности случайной матрицы, обеспечивающий ошибку решения таких задач, близкую к минимальной. The aim is develop a method for determining the optimal size of a random matrix for the method of DIP solving based on the refined evaluation of the input vector. Results and conclusions. The method of DIP solving based on the analytical averaging of random projection has been proposed. For this method, we have developed the criterion for determining the number of rows of a random matrix which provides the error of DIP solution close to the minimum. We conducted an experimental investigation of the accuracy of DIP solution by a deterministic method based on the analytical averaging of random projection with the search for the optimal solution by the model selection criteria of Mallows, Akaike, Minimum description length, and . The experiments showed that and Akaike criteria provide the error value close to the minimum.